Hip to be square : disruption in the U.S. mobile payment market - Markovich, Sarit; Malkani, Anirudh Parasher; Tseng, Andrew; Meagher, Evan ([London] : SAGE, 2016)
Founded in San Francisco in 2009, Square finished 2012 as the darling of Silicon Valley; flush with more than $340 million in funding, the firm had grown to several hundred employees in just three short years. It processed more than $10 billion annually in credit and debit card payments from small business owners that used Square's smartphone-enabled card swipe device wherever cellular or wireless Internet services were available. However, Square's success had attracted new entrants into the mobile payments processing space, both in the United States and abroad, threatening to derail the company's remarkable trajectory. With its latest financing round valuing the company in excess of $3.4 billion, management and investors were considering which strategies would continue, even accelerate, the company's growth.
Originally Published in: Markovich, S., Malkani, A. P., Tseng, A., & Meagher, E. (2014). Hip to be Square: Disruption in the U.S. Mobile Payment Market. 5-213-251. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Mobile commerce -- Case studies; Strategic planning -- Case studies; Business planning -- Case studies